2019
DOI: 10.1002/jimd.12069
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary approach to optimizing glucose‐6‐phosphatase‐α enzymatic activity for gene therapy of glycogen storage disease type Ia

Abstract: Glycogen storage disease type-Ia (GSD-Ia), caused by a deficiency in glucose-6-phosphatase-α (G6Pase-α or G6PC), is characterized by impaired glucose homeostasis with a hallmark hypoglycemia, following a short fast. We have shown that G6pc-deficient (G6pc−/−) mice treated with recombinant adeno-associated virus (rAAV) vectors expressing either wild-type (WT) (rAAV-hG6PC-WT) or codon-optimized (co) (rAAV-co-hG6PC) human (h) G6Pase-α maintain glucose homeostasis if they restore ≥3% of normal hepatic G6Pase-α act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…Therefore, we selected the S298C protein variant for further analysis. This finding is consistent with and supports previous studies by Zhang et al, which reported similar improvements in protein expression with the S298C variant 47 , 48 . Based on predicted topology analysis 49 , the S298C substitution falls within the eighth transmembrane domain of hG6Pase-α, downstream of residues R83, H119, and H176 50 , that are directly involved in hG6Pase-α activity (see predicted topology, Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, we selected the S298C protein variant for further analysis. This finding is consistent with and supports previous studies by Zhang et al, which reported similar improvements in protein expression with the S298C variant 47 , 48 . Based on predicted topology analysis 49 , the S298C substitution falls within the eighth transmembrane domain of hG6Pase-α, downstream of residues R83, H119, and H176 50 , that are directly involved in hG6Pase-α activity (see predicted topology, Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…Their synthetic mRNA, which contained complete N1-methylpseudouridine substitution, and included 5′and 3′untranslated regions along with the coding sequence and a poly(A) tail, was packaged in a LNP formulation and delivered intravenously. Supporting the study of Zhang et al (2019), Cao et al (2021) showed that the G6PC-S298C variant had a 2-fold higher specific activity than WT G6PC, when expressed in vitro, and the activity of the encoded enzyme was further increased by codon-optimization. As previously reported (Zhang et al, 2019), the increase in enzymatic activity of the G6PC-S298C variant correlated with a corresponding increase in the stability of the expressed protein, and notably, the overall clearance rate of G6PC-WT and G6PC-S298C proteins were similar.…”
Section: Mrna Therapy Using a Codon-optimized G6pc-s298c Variantmentioning
confidence: 83%
“…While routinely used in clinical therapies, codon-optimized vectors may not always The effects of codon optimization and catalytic activity optimization are additive and stable. (A) G6pc _/_ mice were treated at age 2 weeks with 10 12 vp/kg rAAV-G6PC-WT, rAAV-G6PC-S298C, rAAV-coG6PC, or rAAV-coG6PC-S298C (n = 6 per group) and analyzed at age 4 weeks (Zhang et al, 2019). (B) G6pc _/_ mice were treated at age 2 weeks with 3 x10 12 vp/kg rAAV-G6PC-WT, rAAV-G6PC-S298C, rAAV-coG6PC, or rAAV-coG6PC-S298C (n = 6 per group) and analyzed at age 66-76 weeks.…”
Section: Strategies To Increase the Expression And Catalytic Activity...mentioning
confidence: 99%
“…infusion n.a. NCT03517085; phase 1/2 2018 Ultragenyx [ 43 ] ABO-102 (scAAV9.U1a.hSGSH) MPS IIIA SGSH AAV9 0.5 × 10 13 1 × 10 13 3 × 10 13 ≥ 6 months, i.v. infusion Signs of efficacy NCT02716246; phase 1/2 NCT04360265 (follow-up) 2016; 2020 Abeona Therapeutics [ 44 ] AT132 X-linked myotubular myopathy hMTM1 AAV8 1 × 10 14 3 × 10 14 ≤ 5 years, males; i.v.…”
Section: Recent Progress Of Aav-based Gene Therapy In Clinicsmentioning
confidence: 99%